Some remarks on a problem in Madhyamaka philosophy of language - Westerhoff, J (John Wiley & Sons Ltd, 2018)
This paper attempts to dissolve an apparent difficulty arising in the philosophy of language as discussed by the Indian Buddhist Madhyamaka school. On the one hand Madhyamaka seems to be claiming that every entity is fundamentally linguistic in nature, on the other hand it also asserts that language does not exist. I argue that the difficulty is to be dissolved by distinguishing two different senses of language appealed to by the Mādhyamikas. They argue that one specific understanding of language is deficient (and that therefore language thus understood does not exist), but this is not the same sense of language according to which everything is linguistic in nature. The apparent contradiction is thereby resolved.